An Item Response Theory Analysis of DSM-5 Heroin Use Disorder in a Clinical Sample of Chinese Adolescents - Yang, Hongmei; Chen, Fu; Liu, Xiaoxiao; Xin, Tao (Frontiers in Psychology, 2019)
The study examined the dimensionality and psychometric properties of DSM-5 criteria for heroin use disorder in a clinical sample of Chinese adolescents using item response theory approach. We examined 168 adolescents aged 14.8 – 17.9, who were in treatment for heroin use disorder. A two-parameter logistic item response theory model was conducted to examine the severity and discrimination of DSM-5 criteria for heroin use disorder. Differential item functioning across age and ethnicity was assessed. Results supported the hypothesis the DSM-5 criteria for heroin use disorder were arrayed an underlying unitary dimension of severity in clinical adolescents. All the items exhibited good discriminatory power in distinguishing between clinical adolescent heroin users. Although three criteria exhibited measurement non-invariance at the item level, the overall DSM-5 heroin use disorder diagnostic criteria set appears to achieve measurement invariance at the scale level.